68Ga DOTATATE PET/CT is an Accurate Imaging Modality in the Detection of Culprit Tumors Causing Osteomalacia. (August 2015) - Zhang, Jingjing; Zhu, Zhaohui; Zhong, Dingrong; Dang, Yonghong; Xing, Haiqun; Du, Yanrong; Jing, Hongli; Qiao, Zhen; Xing, Xiaoping; Zhuang, Hongming; Li, Fang
Abstract : Objectives: Tumor-induced osteomalacia (TIO) is generally caused by small benign mesenchymal tumors producing fibroblast growth factor-23 (FGF-23). The only curative therapy of the disease is resection of the causative tumors. However, these tumors are extremely difficult to detect using conventional imaging modalities. This research was undertaken to evaluate efficacy of 68 Ga DOTATATE PET/CT in this clinical setting. Methods: Images of 68 Ga DOTATATE PET/CT and clinical charts from 54 patients with clinically suspected TIO were retrospectively reviewed. The image findings were compared with the results of histopathological examinations and clinical follow-ups. Results: 68 Ga DOTATATE PET/CT scans were positive in 44 patients, among which, 33 had surgery to remove the lesions. Postsurgical pathological examination confirmed causative tumors in 32 patients whose symptoms diminished promptly, and the serum phosphate levels became normal, which confirmed the diagnoses of TIO. Eleven patients with positive 68 Ga DOTATATE PET/CT did not have surgery. These 11 patients continued to have symptoms and hypophosphatemia but were not included in the final analysis because of lack of evidence to confirm or exclude TIO. Ten patients had negative 68 Ga DOTATATE PET/CT scans. All of these10 patients responded to conservative therapy and had normal serum phosphate levels in the follow-up, which excluded TIO. Therefore, the 68 Ga DOTATATE PET/CT imaging had a sensitivity of 100% (32/32) and a specificity of 90.9% (10/11). The overall accuracy of 68 Ga DOTATATE PET/CT scan in the detection of tumors responsible for osteomalacia is 97.7% (42/43). Conclusions: 68 Ga DOTATATE PET/CT scan is an accurate imaging modality in the detection of tumors causing TIO.